Distribusi Beras Berbasis Offtaker Lokal: Strategi Peningkatan Daya Tawar Petani di Kabupaten Purworejo - Fauzi, Gholib Tamam (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
This study explores the potential of local off-takers in improving the bargaining power of rice farmers in Purworejo, Central Java, by addressing inefficiencies in the current rice distribution system. Despite Purworejo being a major rice producer with an annual average of 279,000 tons, farmers often face low bargaining power due to the long and inefficient supply chain. Farmers typically sell wet paddy to middlemen or collectors at low prices, especially during the harvest season, resulting in incomes below the government's purchasing price. This research uses a qualitative descriptive approach, including literature review, document analysis, and comparative studies from other regions like Kendal, Grobogan, Pinrang, and East Lampung. The findings indicate that the success of the local off-taker model depends heavily on the strength of local institutions, such as cooperatives and BUMDes. In regions with strong institutions like Kendal and Pinrang, the model has stabilized prices and increased farmers' income. Conversely, in Purworejo and East Lampung, weak local institutions prevented competitiveness. This study recommends strengthening local off-taker institutions, enhancing market access, providing financing schemes, and improving post-harvest infrastructure to create a more efficient and equitable distribution system, thereby boosting the competitiveness of local rice and improving farmers' welfare.